A Bibliometric Analysis of Talent Retention Strategies in Technology Companies - Judijanto, Loso; Koesmawan, Koesmawan; Djuanda, Gustian (West Science Interdisciplinary Studies, 2025)
Technology companies compete in a fast‐moving, innovation-driven landscape where retaining highly skilled employees is a strategic imperative. Although a growing body of studies addresses this challenge, the literature is dispersed across disciplines and geographies, obscuring prevailing themes and research gaps. This study conducts a comprehensive bibliometric analysis of 375 peer-reviewed articles (2000-2024) indexed in the Web of Science Core Collection to map the intellectual structure and temporal evolution of research on talent retention strategies in technology companies. Using VOSviewer, we generated keyword co-occurrence, author co-citation, and country collaboration networks, along with density and overlay visualizations. Results show that human resource management, talent management, and employee retention form the field’s foundational core, while emergent themes—innovation, leadership, diversity, and employer branding—have gained prominence since 2020, signaling a shift toward more holistic, employee-centric approaches. Author analysis identifies three influential clusters: methodological rigor (e.g., Ringle, Hair), strategic HRM (e.g., Collings, Cappelli), and cross-cultural HRM (e.g., Budhwar, Warner). Geographically, the United States dominates scholarly output and collaborations, but international linkages remain limited, suggesting opportunities for broader global engagement. The study highlights research gaps in data-driven HR analytics, cross-regional comparisons, and interdisciplinary integration. Findings offer scholars a consolidated research agenda and guide practitioners toward evidence-based, culturally responsive retention strategies that align with evolving workforce expectations.